Assessment of slaughterhouse-based measures as animal welfare indicators in fattening pigs - Hernandez, Rick Obrian; Romero, Marlyn H.; Sanchez, Jorge A. (Frontiers in Animal Science, 2023)
In recent years, there has been growing interest in the assessment of animal welfare in slaughterhouses. The aim of this study was to describe the prevalence of slaughterhouse-based measures as animal welfare indicators and evaluate the relationships between these indicators with sociodemographic characteristics of the drivers and transport conditions in fattening pigs in a commercial slaughterhouse. A total of 1,161 heavy pigs (105.6 kg ± 14.15) that came from 22 commercial farms (one batch/farm) were evaluated. An antemortem assessment of pigs was done during lairaging by evaluating the number, location, and color of skin lesions, tail length, presence of biting lesions, lameness, cough, rectal and vaginal prolapse, and umbilical hernia. Pulmonary lesions, pleuritis, pericarditis, and liver lesions were recorded postmortem. A descriptive analysis was performed on antemortem and postmortem indicators to estimate their prevalence, and the relationships among antemortem and postmortem indicators were inspected through two multilevel mixed-effects models, a lineal regression, and a logistic regression with the farm of origin as a fixed effect. Cough was present in 18.9% (n= 219) of cases, while tail biting lesions (4.6%, n= 53), rectal prolapse (0.1%, n= 11), and vaginal prolapse (0.1%, n= 11) were of low prevalence in this study. Regarding shape of skin lesions, pigs presented linear (55.8%, n= 648), followed by comma (34.7%, n= 403), diffused (6.9%, n= 80) and rectangular lesions (2.5%, n=29). Only 25.2% (n= 512) of lesions had a bright red color. At postmortem, pulmonary lesions were noted in 34.2 ± 13.5 (mean ± SEM) pigs, and these lesions were more prevalent in cranial (11.9 ± 4.9) and medium lobes (12.2 ± 5.2), while caudal (5.3 ± 2.7) and accessory lobes (1.6 ± 1.6) were less affected. The number of skin lesions was significantly associated with drivers’ age, experience in the job, and marital status (p= < 0.001). The tail lesions (presence/absence) were significantly associated with the number of skin lesions, scoring of pulmonary lesions and live weight (p = < 0.001). Antemortem and postmortem indicators at slaughterhouses with low annual slaughter volume can provide information for disease monitoring and animal welfare.